ANALISIS LAJU INFILTRASI TERHADAP MUKA AIRTANAH,KECAMATAN CIPAYUNG, KOTA JAKARTA TIMUR: ANALYSIS OF INFILTRATION RATE OF GROUNDWATER LEVELS IN CIPAYUNG REGION, EAST JAKARTA - Muhammad Yusril Ihza M; Muhammad Adimas Amri; Himmes Fitra Yuda (Journal of Geoscience Engineering & Energy (JOGEE), 2022)
To be able to determine the water catchment area, the value of the infiltration rate and groundwater level are quite important in a parameter for determining the water catchment area, in Jakarta the lack of water catchment areas and the high rate of population growth cause frequent flooding in the capital city, so it is necessary to there is a long-term plan for spatial planning of water catchment areas in Jakarta as one of the steps to overcome flood disasters and become groundwater reserves in the capital city, the higher the groundwater level value in an area, the area has the potential for good catchment areas because it can still accommodate rainwater, infiltration rate data collection was carried out directly in the field using a Double Ring Infiltrometer and for groundwater level data direct measurements were made on dug wells in the study area